Molecular epidemiology of Clostridioides difficile obtained from fecal samples of wild animals in Brazil - Lima, Maiara C. [UNESP]; Basso, Roberta M. [UNESP]; Cerri, Fabrício M. [UNESP]; Lima, Heloísa C. [UNESP]; Rahal, Sheila C. [UNESP]; Zanon, Isabela P.; Carvalho, Gabriela M.; Silva, Rodrigo Otávio S.; Arroyo, Luis G.; Oliveira-Filho, José P. [UNESP]; Borges, Alexandre S. [UNESP] (FapUNIFESP (SciELO), 2024)
Clostridioides difficile is a strictly anaerobic, spore-forming Gram-positive bacterium associated with diarrhea, known as C. difficile infection (CDI). In domestic animals, C. difficile is considered an important pathogen mostly in pigs and horses, but there are also reports in other domestic species. In wild animals, the epidemiology of C. difficile is largely unknown, and the role of the bacterium as a cause of diarrhea is unclear. The aim of this study was to determine the prevalence of C. difficile in the feces of wild animals referred to the Center of Medicine and Research in Wild Animals (CEMPAS). Fecal samples obtained from 100 animals of 34 different species were subjected to qPCR for the detection of the C. difficile 16S rRNA gene and two major toxin genes (tcdA and tcdB) and to anaerobic bacterial isolation. A total of 63 animals (63%) were positive for C. difficile by qPCR, and 16 isolates were recovered. The opossum (Didelphis spp.) had the highest number of positive animals in both tests (from 21 samples, 19 were qPCR positive, and four isolates were recovered). Three toxigenic strains (RT 002, 004, and 014), all previously described as infecting humans and animals, were isolated in the following species: bearded dragon (Pogona vitticeps), pampas fox (Lycalopex vetulus), and marmoset (Callithrix sp.). The presence of C. difficile in the feces of wild animals highlights the importance of wildlife as potential carriers of infection for production animals or humans.
Keywords: Clostridioides difficile; Didelphis spp.; qPCR; tcdA; tcdB; wild animals